2020
DOI: 10.24940/theijbm/2020/v8/i2/bm2002-001
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Customer Satisfaction: A Case Study of Grab in Vietnam

Abstract: Traveling is one of the basic and indispensable needs of each person. The more the society grows, the more demand for travel increases. The transportation service has been put into operation and is growing strongly with many types such as taxi, motorbike taxi. With the development of science and technology, technology has been applied to travel service industry. Recent years in Vietnam, smartphones have become extremely popular, which has led to the development of mobile applications including ride-hailing app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…And [17] incorporates the user's social relationships on this basis, pointing out that different social relationships can infer different attributes. Literature [18] extended the social relations to infer user attributes by visible group information. Besides, [19] proposed an algorithm for inferring user attributes based on community discovery, which can be applied to online social networks, with the algorithmic idea that users with the same attributes are more likely to form community groups with higher aggregation.…”
Section: Related Workmentioning
confidence: 99%
“…And [17] incorporates the user's social relationships on this basis, pointing out that different social relationships can infer different attributes. Literature [18] extended the social relations to infer user attributes by visible group information. Besides, [19] proposed an algorithm for inferring user attributes based on community discovery, which can be applied to online social networks, with the algorithmic idea that users with the same attributes are more likely to form community groups with higher aggregation.…”
Section: Related Workmentioning
confidence: 99%
“…Since optimistic individuals are considered to be happy with the outcomes (Joshanloo et al, 2017), consumers high in optimism tend to be satisfied with the product they are consuming (Westbrook, 1980). For instance, Pham et al (2018) reported that optimistic individuals perceive technology adoption to be useful in their personal and professional lives and that such optimism has a positive association with satisfaction. Similarly, Pham et al (2020) found that optimism positively influenced consumer satisfaction with luxury hotels.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…In other words, they have higher confidence in computers and ability to use computers. Perceived computer self-efficacy, in particular, or technological readiness in general have a positive relationship with perceived ease of use and consumer satisfaction with online commercial applications (Huy et al, 2019;Pham et al, 2018). We can see the online consumer review system as an information technology system; therefore, consumers with higher perceived computer self-efficacy are most likely to perceive that using such a system is not difficult in their purchasing decisions.…”
Section: Perceived Computer Self-efficacymentioning
confidence: 99%